Empires of the Sea : a Maritime Power Networks in World History - Strootman, Rolf,; Eijnde, Floris van den,; Wijk, Roy van, (Cultural Interactions in the Mediterranean ;, 2019)
Empires of the Sea brings together studies of maritime empires from the Bronze Age to the Eighteenth Century. The volume aims to establish maritime empires as a category for the (comparative) study of premodern empires, and from a partly 'non-western' perspective. The book includes contributions on Mycenaean sea power, Classical Athens, the ancient Thebans, Ptolemaic Egypt, The Genoese Empire, power networks of the Vikings, the medieval Danish Empire, the Baltic empire of Ancien Régime Sweden, the early modern Indian Ocean, the Melaka Empire, the (non-European aspects of the) Portuguese Empire and Dutch East India Company, and the Pirates of Caribbean.